2022
DOI: 10.1021/acsami.2c03758
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a 2D/2D g-C3N5/NiCr-LDH Heterostructure to Boost the Green Ammonia Production Rate under Visible Light Illumination

Abstract: Photocatalytic N2 fixation has emerged as one of the most useful ways to produce NH3, a useful asset for chemical industries and a carbon-free energy source. Recently, significant progress has been made toward designing efficient photocatalysts to achieve this objective. Here, we introduce a highly active type-II heterojunction fabricated via integrating two-dimensional (2D) nanosheets of exfoliated g-C3N5 with nickel–chromium layered double hydroxide (NiCr-LDH). With an optimized loading of NiCr-LDH on exfoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Instantly, Che and coauthors reported how to regulate the direction of charge transfer in modified g‐C 3 N 5 to generate H 2 O 2 under visible light illumination. [ 76 ] In this study, they used the doping technique to modulate the electronic structures of g‐C 3 N 5 to reduce oxygen to generate H 2 O 2 efficiently. Specifically, they compared three systems, including pure g‐C 3 N 5 , K, Cl codoped g‐C 3 N 5 , and K, I codoped g‐C 3 N 5 , and disclosed that K, I codoped samples would give significant enhancement in the generation of H 2 O 2 because the modified samples accelerated the kinetic formation rate with enhancing O 2 adsorption properties and extended light absorption capacity with the robust catalysts' stability.…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
“…Instantly, Che and coauthors reported how to regulate the direction of charge transfer in modified g‐C 3 N 5 to generate H 2 O 2 under visible light illumination. [ 76 ] In this study, they used the doping technique to modulate the electronic structures of g‐C 3 N 5 to reduce oxygen to generate H 2 O 2 efficiently. Specifically, they compared three systems, including pure g‐C 3 N 5 , K, Cl codoped g‐C 3 N 5 , and K, I codoped g‐C 3 N 5 , and disclosed that K, I codoped samples would give significant enhancement in the generation of H 2 O 2 because the modified samples accelerated the kinetic formation rate with enhancing O 2 adsorption properties and extended light absorption capacity with the robust catalysts' stability.…”
Section: Photocatalytic Applications Of G‐c3n5‐based Materialsmentioning
confidence: 99%
“…Moreover, in order to prove that the nitrogen gas for the photocatalytic reduction reaction is supplied from the air pump, instead of using the air pump, argon gas was bubbled into the reaction system. Considering that the amount of ammonia production decreased to 664 μmol L –1 g –1 , it shows that nitrogen gas is a key reactant, which is supplied by the air pump. , Using the Watt–Chrisp method, the concentration of hydrazine formed in the photocatalytic nitrogen fixation as an intermediary species was explored, and the results are presented in Figure e . According to this figure, the amount of hydrazine production was almost constant after three hours of exposure to simulated sunlight over the TiO 2 QDs/Fe 3 S 4 20% nanocomposite.…”
Section: Resultsmentioning
confidence: 98%
“…Bharati Debnath [ 70 ] designed a g-C 3 N 5 /NiCr-LDH heterostructure, a hybrid of g-C 3 N 5 and NiCr-layered double hydroxide. DFT calculations showed its ability to adsorb and activate N 2 molecules.…”
Section: Environmental and Energy Applicationsmentioning
confidence: 99%
“… ( a – d ) Initial structure (red circles: the binding position); ( e – h ) corresponding optimized structures; ( i – l ) corresponding N−N bond distances; ( m ) Photocatalytic ammonia production rates of g-C 3 N 5 /NiCr-LDH; ( n ) Schematic illustration of a mechanism for NH 3 production using g-C 3 N 5 /NiCr-LDH; ( o – p ) In-situ DRIFTS spectra of B-C 3 N 5 ; ( q ) NH 3 yields for g-C 3 N 5 and B-C 3 N 5 x (x = 1, 2, 3). ( a – n ) Adapted with permission from [ 70 ]. Copyright Elsevier B.V., 2022.…”
Section: Figurementioning
confidence: 99%